HUBUNGAN ANTARA KEPERCAYAAN DIRI DENGAN KECEMASAN SOSIAL PADA NARAPIDANA MENJELANG BEBAS DI LEMBAGA PEMAYARAKATAN KLAS IIA MUARO PADANG - Ekajaya, Darma Syahrullah; Jufriadi, Jufriadi (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT UPI YPTK PADANG, 2019)
ABSTRACT This study aims to find out and understand self-confidence with social anxiety before free prisoners at Muaro Padang IIA Class Correctional Institution. Variable Dependent in this study is self-confidence and the independent variable is social anxiety. This research is a population research.The sample in this study is prisoners who are free under the guidance of Muaro Padang Class IIA Correctional Institution, which amounts to 72 people. The research method used is quantitative research methods. Measuring instruments used are the self-confidence scale and social anxiety scale, then the data are analyzed using Pearsoncorrelation techniques Product Momentand interpreted based on theories related to the research variables. The results of this study are based on aspects - Aspects of Self Confidence according to Ghufron and Risnawita (2014) and aspects of Social Anxiety according to La Greca and Lopez (1998). Test of validity and reliability usingtechnique Cronbach's Alpha. The results of the validity coefficient on the self-confidence scale ranged from 0.300 to 0.643, while the reliability coefficient was 0.899. The results of the validity coefficient on the social anxiety scale ranged from 0.348 to 0.843, while the reliability coefficient was 0.916. The results of data analysis showed the magnitude of the correlation coefficient of -0.627 with a significant level of p = 0.000 (p <0.01) with an effective contribution of 39% and the remaining 61% was influenced by other factors. This means that there is a negative relationship between confidence in prisoners' social anxiety before being free under the guidance of Muaro Padang Class IIA Correctional Institution.   Keywords: Self Confidence, Social Anxiety, Prisoners